Counterfactuals and Explanatory Pluralism. (4th August 2018) - Khalifa, Kareem; Doble, Gabriel; Millson, Jared
Abstract: Recent literature on non-causal explanation raises the question as to whether explanatory monism, the thesis that all explanations submit to the same analysis, is true. The leading monist proposal holds that all explanations support change-relating counterfactuals. We provide several objections to this monist position. 1 Introduction 2 Change-Relating Monism's Three Problems 3 Dependency and Monism: Unhappy Together 4 Another Challenge: Counterfactual Incidentalism 4.1 High-grade necessity 4.2 Unity in diversity 5 Conclusion